Implementation of Application-Based Accounting and Finance in MSMEs Gresik Regency - Indrawati, Nur Khusniyah; Jazuli, A Muhamad (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: The purpose of community service is to provide an understanding and basic practice of accounting and finance for small and medium scale business activities in Gresik that are application-based. Method: The methods used include lectures, workshops, interactive Q&A, and practical exercises. The activity participants consisted of 29 participants in Gresik. Supporting data was collected through direct observation and interviews with representatives of the small and medium enterprises (SMEs). Practical Applications: There are implications for the participants, including: 1) SMEs need to be disciplined in financial record-keeping, even if the financial records are simple; 2) SMEs are expected to utilize personal or business assets in the form of devices to record business finances using applications; 3) It is hoped that SMEs can continue to grow and open themselves to always learning new things in the disruptive era. Conclusion: The results of the activity show that the implementation of community service went smoothly and received high enthusiasm from the participants. The material provided was in line with the purpose of this community service.